2013
DOI: 10.1177/2325967113502638
|View full text |Cite
|
Sign up to set email alerts
|

A Magnetic Resonance Imaging Study of the Significance of the Distal Femoral Physis During Medial Patellofemoral Ligament Reconstruction

Abstract: Background:Medial patellofemoral ligament (MPFL) reconstruction in adults often utilizes screw fixation in the distal femur. The aim was to define the safety of similar fixation in young patients, with respect to their open physis.Purpose:To define the age-related relationship between the femoral insertion of the MPFL and the medial aspect of the distal femoral physis on magnetic resonance imaging (MRI) scans. The study investigates whether screw fixation at this point is safe with respect to patient age and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 12 publications
(20 reference statements)
0
24
1
Order By: Relevance
“…Ensuring physeal safety during MPFL reconstruction is critical in the skeletally immature population, as the standard adult surgical technique of using screw fixation in the distal femur has been shown to frequently disturb the medial distal femoral physis. 5 An understanding of the close proximity of the MPFL origin to the medial distal femoral physis is important when considering screw placement and trajectory, as placement distal to the physis with a distal oblique trajectory has been shown to safely avoid physeal and joint penetration as compared with parallel screw placement. 5 Determining a safe and anatomic starting point is critical during preoperative planning for MPFL reconstruction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ensuring physeal safety during MPFL reconstruction is critical in the skeletally immature population, as the standard adult surgical technique of using screw fixation in the distal femur has been shown to frequently disturb the medial distal femoral physis. 5 An understanding of the close proximity of the MPFL origin to the medial distal femoral physis is important when considering screw placement and trajectory, as placement distal to the physis with a distal oblique trajectory has been shown to safely avoid physeal and joint penetration as compared with parallel screw placement. 5 Determining a safe and anatomic starting point is critical during preoperative planning for MPFL reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Prior cadaveric and radiographic studies 1,5,8,13,2022 have shown anatomic variation in the distance between the femoral insertion of the MPFL and distal femoral physis, with the distance generally being within millimeters of the physis. Other factors, such as age and sex, have also been suggested to influence this distance in patients with open physes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For pediatric patients, there has been a great deal of investigation into the relationship of the MPFC to the distal femoral physis. There has been wide variability in findings, with the average origin of the MPFC occurring 4.7-10 mm distal to the physis [7,8]. The superior-most fibers of the MPFC origin commonly overlie the physis [7,8].…”
Section: Anatomy and Functionmentioning
confidence: 99%
“…There has been wide variability in findings, with the average origin of the MPFC occurring 4.7-10 mm distal to the physis [7,8]. The superior-most fibers of the MPFC origin commonly overlie the physis [7,8]. The origin may migrate closer to the physis in adolescence [8].…”
Section: Anatomy and Functionmentioning
confidence: 99%